FES202 : Fashion design: form and function / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2019)
The course includes fundamental knowledge of textile technology also form and function in fashion art whereby it emphasizes on the category and practicality of the clothes. Initially students learn to explore the fabric characteristic and behavior to develop design according to their design concept. The final design has to fulfill the requirements of the clothing category. Students also gain skills in material rendering, drawing methods and media handling to produce design portfolio.